Action of plants extract on Trichogrammagalloi (Zucchi, 1988) (Hymenoptera: Trichogrammatidae) - Predes Trindade, Roseane Cristina; de Lima, Ivanildo Soares; Sant'Ana, Antônio Euzébio Goulart; Broglio, Sônia Maria Forti; da Silva, Paulo Pedro (Comunicata Scientiae, 2013)
The plants extract may be compatible with other management tactics, especially with biologicalcontrol. so the aim of this work was to evaluate the residual effect of several extracts from cedartree (C) and mahogany tree (M) (bark (C), wood (M) and leaf (F); cecropia tree (I) (bark - C andwood - M) and of the pereiro (P) (bark -C), and its possible effects on the adults of the parasitoidTrichogramma galloi(Zucchi, 1988) (Hymenoptera: Trichogrammatidae). Cards containingparasitised eggs of Diatraea saccharalis(Fabricius, 1794) (Lepidoptera: Crambidae), or containigeggs that would be submitted to the parasitoid were immersed for 30 seconds in the extracts at 5000μg.mL-1. The number of parasitised eggs and adult emergence of the parasitoid were evaluated.The highest rates of parasitism, up to 60.0%, was obtained by the control treatment, MC, MM, CCand MF, and the treatments that caused a lower percentage of parasitism, IC, IM, PC, CM andCF, respectively. The extracts of different parts of mahogany, which showed a good percentageof parasitism, affected the development of the parasitoid with a low adult emergence. The PCshowed a lower parasitism and emergence. In relation to eggs treated four days after parasitism,it was found that the control treatment had a good average in emergency (98.85%), in the samecategory of treatments IM, CF and CC, respectively. The CC extract was more selective and the PCwas the least selective for T. galloi.